CREATION OF E-LEARNING ENVIRONMENT IN EDUCATIONAL INSTITUTIONS IN THE CONTEXT OF DIGITAL EDUCATION - Bekhzod Sh. Khaitov (International Scientific and Current Research Conferences, 2022)
The article draws conclusions on the creation of an e-learning environment in educational institutions in the context of digitalization of education.